PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN LITERASI SAINS SISWA SD KELAS V PADA MATERI PERISTIWA ALAM - Fatmala, Sindi Ayu; Sujana, Atep; Maulana, Maulana (Jurnal Pena Ilmiah, 2017)
Scientific literacy is a person's ability to understand science. Scientific literacy is important in relation to daily life because by having scientific literacy, someone can consider all its decisions based on the understanding of science that he has. Scientific literacy in Indonesia is still very low. But scientific literacyÂ can be enhanced, one of which is through contextual teaching and learning activities conducted in elementary schools. This is evidenced by the results of research with pre-experimental method with one group pretest-posttest design which shows that contextual learning can increase scienctific literacy in all groups of students whether students in the category high, medium, and low when done properly. There is difference enhance in scientific literacy between students in the category high, medium, and low on aspects of context, content and competence of scientific literacy. But there is no difference in aspects of science attitudes. This increasement difference is supported by different student observation results. The results of high-class student observations are the best of the three and the improvement is so. Nevertheless, the ability of scientific literacy all three can be increased significantly. Thus, contextual teaching and learning has been successful in enhancing studentâ€™s scientific literacy.